The Influence of the Jingsaw Learning Model on Students' Learning Interests at SMA MAN 2 Central Maluku - Rumasukun, Johda; Tetelepta, Edward Gland; Manakane, Susan Evelin (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2024)
Implementing the Jigsaw learning model influences students' interest in learning geography at SMA Man 2 Central Maluku. The quantitative descriptive method describes the positive impact of Jigsaw learning, which creates an interactive situation and stimulates change or development in students. The results of the prerequisite test and hypothesis test show that the data are regular and homogeneous, and the t-test and MANOVA test support that there is a significant influence on students' interest and learning outcomes. This conclusion strengthens the importance of the Jigsaw learning model as an effective method for improving students' interest and learning outcomes.